Spraying-free high-black-brightness high-heat-resistance ASA material and preparation method thereof

By combining a-methylstyrene-styrene-acrylonitrile polymer resin, AS resin, ASA glue powder and high gloss black mother, spray-free high-heat resistance ASA material is prepared, which solves the problem of insufficient heat resistance of existing ASA materials, achieves high heat resistance and spray-free effects and reduces costs.

CN119570171APending Publication Date: 2025-03-07ZHEJIANG KEPUTE NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411788908.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing ASA materials have shortcomings in terms of heat resistance and high heat resistance modification costs, which affects the product surface gloss and blackness, resulting in the inability to achieve the effect of spray-free.

Method used

By combining a-methylstyrene-styrene-acrylonitrile polymer resin, AS resin, ASA glue powder and high gloss black master, etc., the spray-free high black gloss and high heat resistance ASA material is prepared.

Benefits of technology

The high heat resistance of ASA materials is achieved, and the Vica test temperature is ≥100℃, while maintaining the high gloss and blackness of the product surface, achieving the effect of spray-free and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570171A_ABST
    Figure CN119570171A_ABST
Patent Text Reader

Abstract

The invention belongs to an advanced material technology, and relates to ASA material modification, in particular to a spraying-free high-black-brightness high-heat-resistance ASA material and a preparation method thereof.The spraying-free high-black-brightness high-heat-resistance ASA material is obtained by melting and mixing raw materials including AS resin, alpha-methyl styrene-styrene-acrylonitrile polymer resin, ASA rubber powder, color masterbatch and a processing aid. Although the existing formula system can improve heat resistance, the cost is high, and the surface gloss and blackness of a product are easily influenced, so that the spraying-free effect cannot be achieved. The key technology for preparing the high-light, high-brightness and high-heat-resistance ASA material is characterized in that an alpha-methylstyrene-styrene-acrylonitrile polymer resin material with the proportion of poly-alpha-methylstyrene being 40%-50%, ASA rubber powder and color masterbatch are combined, high transparency and good coloring are achieved, the Vicat test temperature of a product is larger than or equal to 100 DEG C, particularly, the surface gloss and blackness of the product are kept, and the heat resistance of the product is improved. And the spraying-free effect is still achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to advanced material technology and relates to ASA material modification, specifically to a spray-free high-black-brightness and high-heat-resistant ASA material and a preparation method thereof. Background Art

[0002] "Spray-free" materials are widely studied and applied to various plastic products because their fundamental purpose of development is to replace the paint spraying process and they are 100% recyclable. Acrylonitrile-styrene-acrylate ternary copolymer (hereinafter referred to as ASA) material is a ternary graft copolymer composed of acrylonitrile (A), styrene (S) and acrylate (A). ASA material is the most cost-effective spray-free matrix material among general engineering plastics. It has good light aging resistance, but its price is almost the same as that of ABS material which has no weather resistance at all. Therefore, it is used by many researchers to develop various spray-free effects. ASA material is a graft copolymer composed of acrylic rubber without double bonds and acrylonitrile and styrene. Because of its excellent light aging resistance, it is widely used for external parts exposed to direct light. However, there are problems such as poor heat resistance or the addition of heat-resistant agents during use, which leads to the surface not being able to achieve high gloss black. Summary of the invention

[0003] At present, the heat-resistant temperature of ASA material itself is relatively low, which limits its application and development in major automotive components, home appliances, office automation equipment, etc. The existing heat-resistant modification cost is high, and it is also easy to affect the surface gloss and blackness of the product, resulting in the failure to achieve the effect of spray-free. The present invention mainly solves the above problems, and prepares a spray-free high-black and high-heat-resistant ASA material with AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch, and processing aid. Through one-time injection molding, a spray-free high-gloss black, heat-resistant high-gloss ASA product can be obtained; further, the high-gloss ASA material has a greater texture and a greater cost advantage.

[0004] The present invention adopts the following technical scheme.

[0005] A spray-free, high-gloss, high-heat-resistant ASA material comprises AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch, and processing aids, wherein the mass proportion of a-methylstyrene segments in the a-methylstyrene-styrene-acrylonitrile polymer resin is 40% to 55%, preferably, the mass proportion of a-methylstyrene segments in the a-methylstyrene-styrene-acrylonitrile polymer resin is 40% to 50%, and further preferably, the mass proportion of a-methylstyrene segments in the a-methylstyrene-styrene-acrylonitrile polymer resin is 42% to 47%; for example, 44%, 45%, 46% and any value within the range. The mass proportion of segments is a conventional concept in the art.

[0006] The invention discloses a method for preparing a spray-free high-black-gloss and high-heat-resistant ASA material. Raw materials including AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch and processing aid are melted and mixed to obtain the spray-free high-black-gloss and high-heat-resistant ASA material.

[0007] Preferably, the spray-free high black gloss and high heat-resistant ASA material of the present invention is obtained by melt-mixing AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch and processing aid as raw materials.

[0008] In the present invention, the masterbatch includes a black masterbatch, with AS as a carrier and a carbon black mass ratio of 30%-60%.

[0009] In the present invention, the processing aid includes one or more of an antioxidant and an anti-ultraviolet agent; preferably, the anti-ultraviolet agent is selected from one or more of UV-770, UV-P, UV-234, UV-360, and UV-329, and the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, and antioxidant 1076.

[0010] In the present invention, the mass ratio of AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, processing aid and masterbatch is (20-40): (30-60): (25-35): (1-2): (3-5); preferably, the mass ratio of AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, processing aid and masterbatch is (20-30): (35-55): (27-32): (1-2): (3-5); further preferably, the mass ratio of AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, processing aid and masterbatch is (20-30): (40-50): (28-32): (1.3-1.8): (3.5-4.5).

[0011] In the present invention, the specific operation of melt-mixing the raw materials to obtain the above-mentioned spray-free high black gloss and high heat-resistant ASA material is a conventional technology, and as an example, it includes the following steps: feeding the raw materials including AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch, and processing aid into a twin-screw extruder, extruding and granulating at 200-240°C to obtain the above-mentioned spray-free high black gloss and high heat-resistant ASA material.

[0012] The invention discloses application of the spray-free high black gloss and high heat-resistant ASA material in preparing spray-free ASA products.

[0013] The invention discloses application of the spray-free high black gloss high heat-resistant ASA material in improving the heat resistance of spray-free high black gloss high ASA products.

[0014] The invention discloses application of the spray-free high-black-gloss and high-heat-resistant ASA material in preparing a spray-free high-black-gloss and high-heat-resistant ASA product.

[0015] The invention discloses application of the above-mentioned spray-free high black gloss and high heat-resistant ASA material in preparing automobile exterior products.

[0016] The invention discloses a spray-free ASA product, and the raw materials for preparing the product include the spray-free high black brightness and high heat resistance ASA material.

[0017] In order to improve the application performance of ASA materials, most of the existing technologies use PMMA alloying, such as CN107501829A discloses a heat-resistant PMMA / ASA alloy for automobiles, CN118440451A discloses a multifunctional scratch-resistant and chemical-resistant PMMA / ASA composition and its preparation method, and CN118185213A discloses a PMMA / ASA composite material and its preparation method and application; some technologies also use PC alloying, such as CN105885379A discloses a scratch-resistant high-gloss spray-free PC / ASA alloy material and its preparation method, and CN112831170A discloses a spray-free matte PC / ASA alloy resin and its preparation method. Although these formula systems can improve heat resistance, they are costly and easily affect the surface gloss and blackness of the product, resulting in the failure to achieve the effect of spray-free. The key technology for preparing the high-gloss, high-brightness, black and high-heat-resistant ASA material of the present invention is to combine a-methylstyrene-styrene-acrylonitrile polymer resin material with a poly-a-methylstyrene ratio of 40%-50%, AS resin, ASA rubber powder and masterbatch, so as to achieve high transparency, good coloring and increase the Vicat test temperature of the product to ≥100°C, especially, maintain the surface gloss and blackness of the product, and still achieve the effect of spray-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a photo of the routine test piece of implementation group 1.

[0019] Figure 2 This is a photo of routine sample preparation for implementation group 1.

[0020] Figure 3 This is a photo of the conventional test piece in comparison group 3.

[0021] Figure 4 This is a photo of the conventional test piece in comparison group 4. DETAILED DESCRIPTION

[0022] At present, the heat-resistant temperature of ASA material itself is relatively low, which limits its application and development in major automotive components, home appliances, office automation equipment, etc. The existing heat-resistant modification cost is high, and it is also easy to affect the surface gloss and blackness of the product, resulting in the failure to achieve the effect of spray-free. The present invention mainly solves the above problems. Through one-time injection molding, a high-gloss ASA with high gloss black and heat resistance can be obtained; further, the high-gloss ASA material has a greater texture and a greater cost advantage.

[0023] The spray-free high black gloss high heat-resistant ASA material of the present invention is obtained by melt mixing AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch and processing aid as raw materials. With AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin and ASA rubber powder as 100%, the formula composition is as follows by mass percentage: AS resin balance a-Methylstyrene-styrene-acrylonitrile polymer resin 35-60% ASA rubber powder 25-35% Preferably, by mass percentage, the formula is as follows: ASA rubber powder 28-32% a-Methylstyrene-styrene-acrylonitrile polymer resin 40-55% AS resin balance As an example, the formula composition is as follows in terms of mass percentage: ASA rubber powder 28-32% a-Methylstyrene-styrene-acrylonitrile polymer resin 40-50% AS resin balance With AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, and ASA rubber powder as 100%, the masterbatch and processing aids are as follows by mass percentage: Processing additives 1-2% AS carrier high gloss black masterbatch 3-5% Preferably, Processing additives 1.2-1.8% AS carrier high gloss black masterbatch 3.5-4.5% Preferably, Processing aids 1.5% AS carrier high gloss black masterbatch 4% The following is a detailed description of the technical progress of the present invention through specific experiments. The raw materials used are all conventional products in the field, and the specific preparation operations and performance tests are all conventional techniques. The materials involved in the examples are described as follows.

[0024] The melt index of a-methylstyrene-styrene-acrylonitrile polymer resin is 8-15g / 10min (220℃+10kg); the experiment adopts: AS-3048Y (poly a-methylstyrene mass accounts for 72%): melt index 9g / 10min (220℃+10kg); AS-8310Y (poly a-methylstyrene mass accounts for 45%): melt index 10g / 10min (220℃+10kg); AS-6310W (poly-a-methylstyrene mass percentage 36%): melt index 10g / 10min (220℃+10kg).

[0025] The melt index of AS resin is 8-15g / 10min (220℃+10kg); the experiment adopts: NX3400: Melt index 12g / 10min (220℃+10kg); NF2200: Melt index 30g / 10min (220℃+10kg).

[0026] ASA rubber powder: 960, Zibo Huaxing. Heat resistant agent: MS-NI (N-PMI), Nippon Denka.

[0027] Other processing aids: a combination of commonly used antioxidants, UV inhibitors, etc.; the experiment used equal amounts of 1010, 770, and 5522, which are conventional commercial products.

[0028] Masterbatch: AS carrier high gloss black masterbatch, 5092 was used in the experiment, from Ningbo Masterbatch Factory.

[0029] In the present invention, the specific operation of melt mixing the raw materials to obtain the above-mentioned spray-free high black gloss and high heat-resistant ASA material is a conventional technology, which includes the following steps as an example: the raw materials including AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch, and processing aid are fed into a twin-screw extruder, extruded and granulated at 200-240°C to obtain the above-mentioned spray-free high black gloss and high heat-resistant ASA material. Specifically, the raw materials used are directly mixed and then enter the twin-screw extrusion melt processing, or a single material can be added to the extruder separately through a loss-in-weight metering scale, and the processing aid and carbon black masterbatch are mixed together and added through a single loss-in-weight metering scale; the twin-screw equipment used can have a diameter of 30-75mm, a rotation speed of 300-1200rpm, and a temperature of 210-240°C for processing, molding and granulation.

[0030] In the examples and comparative examples, the materials used are conventionally mixed and directly put into a twin-screw extruder for melting and processing. The twin-screw equipment used has a diameter of 60 mm, a rotation speed of 800 rpm, and a temperature of 210-240° C. for processing and granulation.

[0031] The material testing method is conventional technology, and the experiment is briefly described as follows.

[0032] Melt index: According to ISO 1133, 220℃, 10kg; requirement ≥8 g / 10min.

[0033] Gloss: At room temperature of 23±2℃, use a gloss meter to test the injection molding samples of the same mold. According to the standard GB / T 1743, the gloss at a 60° angle is required to be ≥96gloss.

[0034] Appearance color: At room temperature of 23±2℃, use a colorimeter to test the injection molded samples of the same mold, and require the L value to be ≤4.5. Visual inspection should achieve a high-gloss black paint effect without pitting.

[0035] Weathering requirements: According to SAE J2527 standard test for 1894h, color fastness grayscale level ≥ 4; no change in appearance or touch (such as no crow's feet, swelling, cracks, softening, or cracking compared to the state submitted for inspection).

[0036] Izod notched impact strength (23°C): Tested in accordance with the method specified in GB / T 1843. Sample size: (80±2) mm×(10±0.2) mm×(4±0.2) mm, 2.75J pendulum, notch type: A type, the notch should be machined after the spline is injection molded. Required ≥10KJ / m 2 .

[0037] Vicat softening temperature: Tested in accordance with the B50 method specified in GB / T 1633. Sample size: (10±2) mm×(10±0.2) mm×(4±0.2) mm, required to be ≥100°C, in order to meet the high heat resistance requirements of automotive exteriors.

[0038] The raw material formula of the embodiment and the comparative example is shown in Table 1, and the performance test is shown in Table 2. The present invention obtains an ASA material with qualified impact resistance by selecting the ratio of poly-a-methylstyrene, combining ASA rubber powder, carrying AS resin and masterbatch, and the surface gloss reaches above 98gloss (60° angle), and the surface blackness reaches the blackness of high-gloss spray paint (L value below 4.5), and the Vicat data can also reach above 100°C, and the notched impact strength is greater than 10kJ / m 2 ; and the cost increase is very small, much lower than the existing heat-resistant modification cost.

[0039] Table 1 Raw material formula of examples and comparative examples, Kg

[0040] Table 2 Performance of the products of the embodiments and comparative examples

[0041] Cost considerations are based on Comparative Example 1, and the cost increases of each modified system are compared, calculated based on the current market price of raw materials. Comparative Example 2 has a 50% cost increase over Comparative Example 1, and a-methylstyrene-styrene-acrylonitrile polymer resin (40Kg) has a cost increase of less than 30% over Comparative Example 1.

[0042] The applicant previously provided a highly weather-resistant, high-gloss white spray-free ASA material and a preparation method thereof. The glossiness and scratch resistance of the material meet the standards for exterior trim, but cannot meet the high heat resistance requirements for automotive exterior trim.

[0043] On the basis of Example 1, 70 kg of AS-8310Y is used, that is, NF2200 is replaced by AS-8310Y. The melt index is too small, which is 5 g / 10 min, but its cost is increased by 70% compared with Comparative Example 1.

[0044] It can be seen from the experiment that the heat-resistant agent MS-NI commonly used in this field leads to unqualified appearance and affects the high black and bright effect; another conventional heat-resistant agent a-methylstyrene is not suitable for this system.

[0045] Figure 1 To implement the routine test piece photos of Group 1, Figure 2 To implement the routine sample preparation photos of Group 1, Figure 3 For comparison, the conventional test piece photos of group 3 are shown. Figure 4 This is a photo of the conventional test piece in comparison group 4.

[0046] In recent years, the application of high-gloss automotive interior and exterior trims has gradually increased; among them, automotive interior and exterior trims (especially exterior trims) have high requirements for product heat resistance and weather resistance. Relevant industry standards require that the Vicat softening temperature of automotive exterior trims must reach above 100°C and the weather resistance must be qualified after aging with a xenon lamp for 1894 hours. With the rapid development of the automotive industry, the application requirements of such products will be further improved. The existing technology uses PMMA with maleimide heat-resistant agents to prepare heat-resistant spray-free ASA materials, which is costly and easily affects the surface gloss and blackness of the product, resulting in the failure to achieve the effect of spray-free; the existing heat-resistant agents either lead to unqualified appearance, affecting the high black and bright effect, or cannot be applied to the ASA system. The present invention obtains an ASA material with qualified impact resistance by selecting the ratio of poly-a-methylstyrene, combining ASA rubber powder, carrying AS resin and high-gloss black masterbatch, and its surface gloss reaches above 98gloss (60° angle), while the surface blackness reaches the blackness of high-gloss spray paint (L value below 4.5), Vicat data can also reach above 100°C, and the notched impact strength is greater than 10kJ / m 2 ; and the cost increase is very small, much lower than the existing heat-resistant modification cost.

Claims

1. A spray-free, high-gloss, high-heat-resistant ASA material, comprising AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch, and processing aid, characterized in that: In the a-methylstyrene-styrene-acrylonitrile polymer resin, the mass proportion of the a-methylstyrene chain segment is 35% to 45%.

2. The spray-free high black gloss and high heat-resistant ASA material according to claim 1, characterized in that: The mass ratio of AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, processing aid and masterbatch is (20-40): (30-60): (25-35): (1-2): (3-5).

3. The method for preparing the spray-free high-gloss and high-heat-resistant ASA material according to claim 1, characterized in that: Raw materials including AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, masterbatch and processing aid are melted and mixed to obtain a spray-free, high-gloss and high-heat-resistant ASA material.

4. The method for preparing the spray-free high-gloss and high-heat-resistant ASA material according to claim 3, characterized in that: The masterbatch includes a black masterbatch; the processing aid includes one or more of an antioxidant and an anti-ultraviolet agent.

5. The method for preparing the spray-free high-gloss and high-heat-resistant ASA material according to claim 3, characterized in that: The mass ratio of AS resin, a-methylstyrene-styrene-acrylonitrile polymer resin, ASA rubber powder, processing aid and masterbatch is (20-30): (35-55): (27-32): (1-2): (3-5).

6. The method for preparing the spray-free high-gloss and high-heat-resistant ASA material according to claim 3, characterized in that: Melt mixing takes place in an extruder.

7. Use of the spray-free high black gloss and high heat-resistant ASA material according to claim 1 in the preparation of spray-free ASA products.

8. Use of the spray-free high black gloss and high heat-resistant ASA material according to claim 1 in improving the heat resistance of spray-free high black gloss and high ASA products.

9. Use of the spray-free high-gloss and high-heat-resistant ASA material according to claim 1 in the preparation of spray-free high-gloss and high-heat-resistant ASA products.

10. A spray-free ASA product, characterized in that: The preparation raw materials include the spray-free, high-gloss, and high-heat-resistant ASA material as described in claim 1.

Citation Information

Patent Citations

  • Scratch-resistant high-gloss spraying-free PC / ASA alloy material and preparation method thereof

    CN105885379A

  • Car heat-resistant grade spray-free PMMA / ASA alloy

    CN107501829A

  • Spraying-free matte PC / ASA alloy resin and preparation method thereof

    CN112831170A

  • PMMA / ASA composite material as well as preparation method and application thereof

    CN118185213A

  • Multifunctional scratch-resistant and chemical-resistant spraying-free PMMA / ASA composition and preparation method thereof

    CN118440451A